Obstetric outcomes in women with congenital heart disease and residual right ventricular outflow tract lesions. (16th November 2010) - Khalil, A; Greutman, M; Brooks, R; O'Brien, P; Walker, F
Abstract : Background: Current evidence suggests that the cardiovascular demands of pregnancy increase fetal morbidity in women with residual right ventricular outflow tract (RVOT) lesions, particularly if there are severe maternal haemodynamic residua. However, data are limited. Methods: In a retrospective cohort study in women with operated and un-operated congenital RVOT Obstruction (RVOTO), pregnancy outcomes were compared with those in the general population. Results: The authors identified 93 pregnancies in 48 women: 36 with surgically corrected Tetralogy of Fallot (TOF), 44 Pulmonary Stenosis (PS) (31 operated), 8 Pulmonary Atresia (all operated), 5 others. There were no maternal deaths. There were 12 (13%) spontaneous abortions (9 early) and 5 terminations. Of 76 pregnancies reaching viability, 9 (12%) were born ≤34 weeks (all for obstetric reasons), 2 (3%) of which were stillborn (one 24 weeks, cause unknown; the second 34 weeks, with placental insufficiency). Mean birth weight of those delivered ≥37 weeks was 3160 g. Four infants had congenital heart disease, including TOF, PS, patent ductus arteriosus and atrial septal defect; only one required surgical correction. 52 (68%) women delivered vaginally, 34 laboured spontaneously and 18 were induced. 24 (32%) delivered by Caesarean section (CS), all for obstetric reasons, apart from one elective CS for maternal cardiac indication. 13 (17%) pregnancies had obstetric complications, including 4 (5%) with cervical incompetence, 2 (3%) each with chronic hypertension, pre-eclampsia, postpartum haemorrhage. Conclusion: This is the largest series describing obstetric outcomes in women with RVOTO. Stillbirths and preterm delivery before 34 weeks were more common than in the general population, but other pregnancy complications were not. All preterm deliveries were due to obstetric reasons.